Analisis Keselamatan dan Kesehatan Kerja Menggunakan Metode Hazard Identification, Risk Assessment, Risk Control pada Divisi Kendaraan Khusus PT Pindad - Rustiya Noorbasara; Resi Juariah Susanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to analyze the application of occupational safety and health in the Special Vehicle Division of PT Pindad using hazar indentification, risk assessment, and risk control methods. The focus of the research is to identify potential hazards, assess the level of risk, and evaluate risk control efforts in the production process of the Special Vehicle Division. The research method used is descriptive with a quantitative approach. The data used in this study was obtained from the results of interviews and direct observations at the company. The results of this study show that there are 5 activities that are identified as causing potential danger, and the risk rating is determined, namely the first activity has a medium risk value, the second activity has a low risk value, the third activity has a negligible risk value, the fourth activity has a high risk value, and the fifth activity has a medium risk value, as well as administrative control efforts, technical control, and PPE control.